Апперкот: [роман] / Сергей Протасов - Протасов Сергей Альбертович (Военная фантастика, 2020)
Экземпляры: ЦБ (20230508) / Инвентарный номер: 57019 / Цена: 365.53 / Сис.шифр: 84(2=411.2)6 / Авт.знак: П 83 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-44